THE EFFECT OF HEALTHY BALANCE OF INFANT MORTALITY RATE - Dian Rizaqi Widiani; Rahmadilla Meulita Afriani; Andika Pratama; Fahmi Arif Kurnianto; Fahrudi Ahwan Ikhsan (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2019)
In Indonesia the number of infant mortality rate is still high. The mortality rate is a sensitive indicator of the state of health status in a community. Health problems that can directly affect infant mortality, maternal and child health, economic and social conditions, residential areas, etc. In each province the number of infant mortality varies. Usually every year the number of numbers can be increased from the previous figure. The condition of each environment will affect the health of the surrounding community. To improve public health it is necessary to consider the basic human needs to obtain a healthy and comfortable environment. Such as providing clean water, food, and a clean and comfortable place to live. That way can reduce infant mortality rate which is currently still quite high. Below is the data of Infant Mortality Rate from each Province in Indonesia that is equal to and above average. Data collection technique using secondary data sourced from BPS and komenkes. Data analysis technique data analysis used is product moment correlation to know strength of relation between 2 variables. Based on data we collected from the Central Bureau of Statistics and the Ministry of Health, the death toll in some areas is still very high. Also the lack of healthy regional governance is one of the factors of high infant mortality rate. From the data that has been calculated using correlation can yield a number of -0.536742675 where if the result minus (-) then shows a strong relationship between two variables. It proves that the relationship between infant mortality and healthy area is strong. In addition, healthy regional governance can also show the high infant mortality rate. Keyword : social conditions, health status, mortality rate Kementerian Kesehatan Republik Indonesia. (2016). Profil Kesehatan Indonesia. Profil Kesehatan Provinsi Bali. Supraptini, Tin Afifah. 2006 Kondisi Kesehatan Ligkungan di Indonesia dan Angka Kematian Bayi, Angka Kematian Balita Serta Kematian Balita menurut data Susenas 1996, 2001 dan 2003 Tri Arifah Ashani, 2007 KEMATIAN BAYI MENURUT KARAKTERISTIK DEMOGRAFI DAN SOSIAL EKONOMI RUMAH TANGGA DI PROPINSI JAWA BARAT IFA, Hoday et al. ANALISIS SOSIAL EKONOMI TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT TENGGER GUNUNG BROMO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 169-175, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12305>. Date accessed: 12 aug. 2019. PAHLEVY, Fahrizal Novan; APRIYANTO, Bejo; ASTUTIK, Sri. KARAKTERISTIK SOSIAL EKONOMI MASYARAKAT DAERAH WISATA BROMO SEBAGAI PENGEMBANGAN KESEJAHTERAAN HIDUP. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 172-189, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12177>. Date accessed: 12 aug. 2019. HARYANTI, Titik Umaiyah. PERANAN PANTAI DALAM KONDISI SOSIAL EKONOMI MASYARAKAT DISEKITAR PANTAI BENTAR KABUPATEN PROBOLINGGO JAWA TIMUR.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 1, n. 1, p. 12-16, aug. 2018. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/8336>. Date accessed: 12 aug. 2019. UMAM, Muhammad Fikri; ALHIDAYAH, Yazid; FAUZIYAH, Rita. ANALISIS MATERIAL ENDAPAN VULKAN GUNUNG SEMERU KABUPATEN LUMAJANG. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 92-98, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11522>. Date accessed: 12 aug. 2019. SETYAWAN, Muhammad Alif; APRIYANTO, Bejo; ASTUTIK, Sri. ANALISIS KARAKTERISTIK ENDAPAN MARINE DAN PENGARUHNYA BAGI SEKTOR PERTANIAN DAN PERAIRAN DI PESISIR SELATAN PANTAI PANCER KECAMATAN PUGER KABUPATEN JEMBER JAWA TIMUR. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 141-154, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11760>. Date accessed: 12 aug. 2019. KURNIANTO, Fahmi Arif et al. THE ENVIRONMENT ANALYSIS OF POPULATION GROWTH, UNEMPLOYMENT, AND POVERTY LEVEL IN MAESAN DISTRICT BONDOWOSO REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 2, p. 113-121, aug. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/8439>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i2.8439. SARI, Eva Kurnia; PRAMESTY, Dinda Ayu. THE EFFECT OF VEHICLES INTENSITY IN SUMBERSARI JEMBER REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 3, p. 50-58, jan. 2019. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/9300>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i3.9300. LESTARI, Dwi et al. ANALISIS FENOMENA GEOGRAFI FISIK PADA PENGUKURAN PROSES DAN HASIL PROSES BENTANG ALAM JAWA TENGAH. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 110-118, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11626>. Date accessed: 12 aug. 2019. ZAHROH, Faidatuz; ELFIANI, Vira; H, Arya Bagas. ASPEK SOSIAL DAERAH KARST PUGER DALAM PRESPEKTIF EKONOMI. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 155-160, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11780>. Date accessed: 12 aug. 2019. NURIYANTO, Muhammad Zaid; FIRMANSYAH, Fahrul Agil; PRASETYONO, Ica. ANALISIS PERUBAHAN BENTANG GEOMORFOLOGI PANTAI BENTAR KABUPATEN PROBOLINGGO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 99-109, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11523>. Date accessed: 12 aug. 2019.